2012
DOI: 10.1037/a0023533
|View full text |Cite
|
Sign up to set email alerts
|

Walk on the bright side: Physical activity and affect in major depressive disorder.

Abstract: Although prescribed exercise has been found to improve affect and reduce levels of depression, we do not know how self-initiated everyday physical activity influences levels of positive affect (PA) and negative affect (NA) in depressed persons. Fifty-three individuals diagnosed with Major Depressive Disorder (MDD) and 53 never-depressed controls participated in a seven-day experience sampling study. Participants were prompted randomly eight times per day and answered questions about their physical activity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
166
6
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(205 citation statements)
references
References 72 publications
22
166
6
4
Order By: Relevance
“…Some studies have shown that even though temperamental variables reduce during treatment, the difference between treatment and control groups increases over time (53). Moreover, previous studies have indicated that changes in temperamental variables, such as positive affect, are related to the dosage of medication (54). Thus, in contrast with traditional concepts, various studies have shown that temperament may change over time and in response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that even though temperamental variables reduce during treatment, the difference between treatment and control groups increases over time (53). Moreover, previous studies have indicated that changes in temperamental variables, such as positive affect, are related to the dosage of medication (54). Thus, in contrast with traditional concepts, various studies have shown that temperament may change over time and in response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The type of goal allows us to distinguish between sport and physical activity (PA): sport performance vs. psychophysical health. Health-oriented physical activity increasingly attracts the interest of researchers, for the results suggest that PA has a beneficial influence not only on physical health, but also on mental health, e.g., in the case of people suffering from depression (Mata et al, 2012), anxiety disorders (Meng & D'Arcy, 2013), eating disorders (Joseph, Alonso-Alonso, Bond, Pascual-Leone, & Blackburn, 2011;Lipowski, Buliński, & Krawczyński, 2009) as well as in treatment of alcohol-dependent individuals (Lipowski, Szulc, & Buliński, 2015), or drug addicts (Lynch, Peterson, Sanchez, Abel, & Smith, 2013). Systematic engagement in physical activity is recommended not only to children (Gubbels, Van Kann, de Vries, Thijs, & Kremers, 2014), adolescents (Biddle & Asare, 2011), adults, and elderly people (Middelweerd, Mollee, van der Wal, Brug, & te Velde, 2014), but also to pregnant women (Guszkowska & Langwald, 2014).…”
Section: Inventory Of Physical Activity Objectivesa New Methods Of Meamentioning
confidence: 99%
“…Se ha demostrado el efecto positivo que tiene en humanos la actividad física sobre el estado de ánimo y el control de las crisis epilépticas (75)(76)(77). Ratas con depresión de la especie SwLo sometidas a actividad física se compararon con controles sin exposición al ejercicio.…”
Section: ¿Cómo Se Explica La Mejoría De La Comorbilidad Depresiva Enunclassified